Knowledge, attitudes, practices, and self-efficacy of the Chinese public regarding cardiopulmonary resuscitation: an online cross-sectional survey - Gao, Huiming; Liu, Xiaohui; Jiang, Zhixia; Huang, Shiming; Pan, Xiaoying; Long, Jianmei; Tong, Qingqing; Li, Li; Zhou, Manhong; Hu, Rujun (Frontiers in Public Health, 2024)
Objective To evaluate the current status of Chinese public’s knowledge, attitudes, practices (KAP) and self-efficacy regarding cardiopulmonary resuscitation (CPR), and to analyze the factors that influence KAP and self-efficacy. Methods An online cross-sectional survey was conducted from February to June 2022 in Mainland China via a self-designed self-filled questionnaire. Potential participants were recruited through WeChat by convenience sampling and snowball sampling methods. Descriptive and quantitative analyses were used for statistical analysis. Results The survey included 4,450 participants from 31 provinces, autonomous regions, or municipalities across Mainland China, aged 18 or above. The public’s average understanding (clear and very clear) of the knowledge regarding CPR was 67.4% (3,000/4,450), with an average proportion of positive attitudes at 96.8% (4,308/4,450). In practice, the average proportion of good practices was 92.8% (4,130/4,450), while the percentage of good self-efficacy averaged at 58.9% (2,621/4,450), only 42.4% (1,885/4,450) of the participants had confidence in the correct use of automated external defibrillator (AED). Pearson correlation analysis showed a significantly positive correlation among knowledge, attitude, practice, and self-efficacy (p < 0.01). Multiple linear regression analysis revealed that several factors have a significant influence on the public’s CPR KAP and self-efficacy, including ever having received CPR training (p < 0.001), hearing about AED (p < 0.001), performing CPR on others (p < 0.001), hearing about CPR (p < 0.001), occupation (p < 0.001), personal health status (p < 0.001), education level (p < 0.001), gender (p < 0.001), and encountering someone in need of CPR (p = 0.021). Conclusion The Chinese public demonstrates good knowledge of CPR, positive attitude, and high willingness to perform CPR. However, there is still room for improvement in the mastery of some professional knowledge points related to CPR and AED. It should be noted that knowledge, attitude, practice, and self-efficacy are interrelated and influence each other. Factors such as prior CPR training, hearing about AED, having performed CPR before, hearing about CPR, occupation, personal health status, education level, gender, and having encountered someone in need of CPR have a significant impact on the public’s KAP and self-efficacy.